1962
DOI: 10.1083/jcb.14.1.65
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Annuli as Pathways for Nucleocytoplasmic Exchanges

Abstract: Colloidal gold particles, 25 to 55 A in diameter, which had been coated with polyvinylpyrrolidone, were microinjected into the ground cytoplasm of amebas (Chaos chaos). At time intervals of I minute, 2 minutes, 10 minutes, and 24 hours after injection the cells were fixed for electron microscopy. After 24 hours, gold particles were found in both the nuclei and the ground cytoplasm, the concentration being higher in the nuclei. Colloidal particles were also present in the nuclei after 10 minutes, but at this ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

1965
1965
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(47 citation statements)
references
References 10 publications
(11 reference statements)
2
45
0
Order By: Relevance
“…The variations in incidence and distribution of nuclear pores in the developing megasporocyte of Dendrobium do not seem unusual when viewed in the light of the many qualitative and quantitative changes exhibited by other components of the same cell, and by the many dynamic alterations which occur in the nuclear envelopes of other organisms (e.g., KAUFMANN and GAY 1958, PEVELING 1961, LINNANE et al 1962. FELDHERR (1962) has demonstrated that annulate regions in the nuclear envelope provide pathways for the intracellular movement of foreign particles. Whether or not the lack of pores in the envelope of the enlarged prophase I nucleus is associated with significant physical and biochemical activity within the developing cell under examination remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The variations in incidence and distribution of nuclear pores in the developing megasporocyte of Dendrobium do not seem unusual when viewed in the light of the many qualitative and quantitative changes exhibited by other components of the same cell, and by the many dynamic alterations which occur in the nuclear envelopes of other organisms (e.g., KAUFMANN and GAY 1958, PEVELING 1961, LINNANE et al 1962. FELDHERR (1962) has demonstrated that annulate regions in the nuclear envelope provide pathways for the intracellular movement of foreign particles. Whether or not the lack of pores in the envelope of the enlarged prophase I nucleus is associated with significant physical and biochemical activity within the developing cell under examination remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In quiescent, nondividing cells, the NE acts as a selective barrier around the nucleus that impedes nuclear import of pDNA and nonviral gene delivery systems. Feldherr described in 1962 that nucleocytoplasmic transport of colloidal gold particles occurs through specialized pores in the NE, the so-called nuclear pore complexes (NPCs) (5). In addition, Bonner showed that protein migration into the nuclei is restricted to small proteins and nuclear proteins (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The import and export of proteins and other macromolecules into or from nuclei and resealed nuclear envelopes is mediated by pore complexes embedded in the nuclear envelope (Bonner, 1975;Riedel and Fasold, 1987a, b;Feldherr, 1962;Stevens and Swift, 1966). The passage of proteins and RNP particles through the pore complex is restricted by the size of the particles (Feldherr, 1972;Paine and Feldherr, 1972), but, in addition, the selectivity of translocation depends on signal sequences within the mature macromolecules (Kalderon et al, 1984;Dabauville and Franke, 1982;Dingwall et aL, 1982).…”
Section: Introductionmentioning
confidence: 97%